1988
DOI: 10.1042/bj2510527
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic trapping of intermediates of the scallop heavy meromyosin adenosine triphosphatase reaction revealed by formycin nucleotides

Abstract: The kinetics of interaction of formycin nucleotides with scallop myosin subfragments were investigated by exploiting the fluorescence signal of the ligand. Formycin triphosphate gives a 5-fold enhancement of the emission intensity on binding to heavy meromyosin, and the profile indicates that the kinetics of binding are Ca2+-insensitive. In contrast, the subsequent product-release steps show a marked degree of regulation by Ca2+. In the absence of Ca2+ formycin triphosphate turnover by the unregulated and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 39 publications
(47 reference statements)
3
43
0
Order By: Relevance
“…This method is suitable for samples of myosin in the filamentous state and gives good signal/noise ratio, and the physiological substrate (ATP) can be used. The single turnovers of scallop myosin with [␥-32 P]ATP provided further support for the presence of a refractory state (24), since the amount of P i bound at the ATPase site increased with the concentration of ATP with ratios of ATP/myosin heads of greater than 1. This is what would be expected with an excess of ATP over myosin heads according to Scheme I.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This method is suitable for samples of myosin in the filamentous state and gives good signal/noise ratio, and the physiological substrate (ATP) can be used. The single turnovers of scallop myosin with [␥-32 P]ATP provided further support for the presence of a refractory state (24), since the amount of P i bound at the ATPase site increased with the concentration of ATP with ratios of ATP/myosin heads of greater than 1. This is what would be expected with an excess of ATP over myosin heads according to Scheme I.…”
Section: Discussionmentioning
confidence: 95%
“…To explain the slow turnover rates of scallop myosin and scallop HMM in the presence of EGTA, Jackson and Bagshaw (24) proposed the following scheme (Scheme I) that was based on the results of single turnover experiments of the regulated scallop HMM with the ATP analogue FTP. They suggested that in the presence of EGTA the rate constants k 3 and k ϩr are comparable, whereas k Ϫr Ͻ Ͻ k 3 or k ϩr .…”
Section: Discussionmentioning
confidence: 99%
“…The results of these conformational changes have been seen in electron micrographs in which the heads on myosin filaments shift from an ordered array in the absence of Ca2+ to a disordered array in its presence (19). Kinetic studies of the scallop myosin ATPase (12,20,21) have suggested that Ca2+ binding to the myosin causes conformational changes at both the purine and phosphate binding sites. However, no information is available about specific amino acids within the active site that may be involved with the conformational changes associated with Ca2+ regulation.…”
mentioning
confidence: 89%
“…Therefore, the proteins measurable by the bioluminescence method are limited. Similarly, the enzymatic assay to quantify the amount of ADP with pyruvate kinase/lactate dehydrogenase or hexokinase/ glucose-6-phosphate dehydrogenase (13) or quantify the amount of P i with P i -binding protein (14) seem to be limited.…”
mentioning
confidence: 97%